Підготовка 2D концепт-арту до використання у наступних етапах розробки проєкту - Страшко, Д. А. (ХНУРЕ, 2025)
The preparation of 2D concept art for 3D development is a crucial stage in production, ensuring clear and detailed references for accurate model creation. The objective of this study is to determine the key aspects of 2D concept art development to improve the workflow of 3D artists. A structured approach ensures a seamless transition from 2D concept art to 3D modeling, enhancing accuracy and efficiency in the production pipeline.
Keywords: 2D концепт-арт; 2D concept art